Evaluation of Vaginoplasty Outcomes Using Skin Grafts versus Amniotic Membrane: A Comparative Cross Sectional Study - karki, Gyanendra Man Singh; Pandey, Shuvechha; Dahal, Prerana; KC, Heera (Birat Journal of Health Sciences, 2025)
Introduction: Vaginoplasty is a reconstructive surgical procedure for vaginal agenesis or other indications. Traditional techniques involve the use of skin grafts, while the amniotic membrane has emerged as a promising alternative due to its better compliance and healing properties.Objectives: The objective was to compare the outcomes of vaginoplasty performed using skin grafts versus amniotic membranes.Methodology: A comparative cross-sectional study was conducted at a tertiary care center from June 30, 2023 to June 30, 2025, involving 15 female patients who underwent vaginoplasty. Of these, 5 received autologous skin grafts and 10 received preserved human amniotic membranes. Patients with no prior vaginoplasty and without contraindications for elective surgery were included. Ethical approval was obtained, and informed consent was secured. Clinical outcomes such as operative time, blood loss, postoperative pain, mold duration, epithelialization, UTI, vaginal stenosis, final vaginal length, complications, and compliance were assessed. Data were collected via a structured proforma, followed up telephonically, and analyzed descriptively using Microsoft Excel 2016.Results: A total of 15 patients aged 16–24 years were included, with 5 undergoing vaginoplasty using skin grafts and 10 using amniotic membrane graft. Operative time and blood loss were higher in the skin graft group (60–120 min; 40–80 mL) compared to the amniotic membrane group (35–60 min; 20–40 mL). Postoperative pain scores on Day 1 were also higher in the skin graft group (7.2 ± 1.1 vs. 4.5 ± 0.9). Epithelialization was good in both groups. One UTI occurred in each group. At 3-month follow-up, vaginal stenosis was observed in one skin graft and three amniotic membrane cases. The mean final vaginal length was 9 cm in the skin graft group and 8 cm in the amniotic group. No major complications were reported. Patient compliance was better in the amniotic membrane group, likely due to reduced pain and faster recovery.Conclusion: Vaginoplasty with amniotic membrane showed faster recovery and better patient comfort, while skin grafts provided slightly superior anatomical outcomes. Both techniques were safe with minimal complications.